Foam-mat drying technology: A review. Issue 12 (13th August 2017) - Hardy, Z.; Jideani, V. A.
ABSTRACT: This article reviews various aspects of foam-mat drying such as foam-mat drying processing technique, main additives used for foam-mat drying, foam-mat drying of liquid and solid foods, quality characteristics of foam-mat dried foods, and economic and technical benefits for employing foam-mat drying. Foam-mat drying process is an alternative method that allows the removal of water from liquid materials and pureed materials. In this drying process, a liquid material is converted into foam that is stable by being whipped after adding an edible foaming agent. The stable foam is then spread out in sheet or mat and dried by using hot air (40–90°C) at atmospheric pressure. Methyl cellulose (0.25–2%), egg white (3–20%), maltodextrin (0.5–05%), and gum Arabic (2–9%) are the commonly utilized additives for the foam-mat drying process at the given range, either combined together for their effectiveness or individual effect. The foam-mat drying process is suitable for heat sensitive, viscous, and sticky products that cannot be dried using other forms of drying methods such as spray drying because of the state of product. More interest has developed for foam-mat drying because of the simplicity, cost effectiveness, high speed drying, and improved product quality it provides.